Cognitive Wireless Networks - Feng, Zhiyong; Zhang, Qixun; Zhang, Ping. (Springer, 2015)
This brief examines the current research in cognitive wireless networks (CWNs). Along with a review of challenges in CWNs, this brief presents novel theoretical studies and architecture models for CWNs, advances in the cognitive information awareness and delivery, and intelligent resource management technologies. The brief presents the motivations and concepts of CWNs, including theoretical studies of temporal and geographic distribution entropy as well as cognitive information metrics. A new architecture model of CWNs is proposed with theoretical, functional and deployment architectures supporting cognitive information flow and resource flow. Key technologies are identified to achieve the efficient cognitive information awareness and delivery. The brief concludes by validating the effectiveness of proposed theories and technologies using the CWNs testbed and discussing the importance of standardization practices. The context and analysis provided by this text are ideal for researchers and practitioners interested in wireless networks and cognitive information. Cognitive Wireless Networks is also valuable for advanced-level students studying resource management and networking.
Keywords: Computer communication systems; Electrical engineering; Information storage and retrieval; Computer Communication Networks; Communications Engineering, Networks; Information Storage and Retrieval